2019
DOI: 10.3390/cells8070665
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma-Derived Extracellular Vesicles Bear the Potential for the Induction of Antigen-Specific Tolerance

Abstract: Background: Cancer-induced immunosuppression is antigen-specific rather than systemic and the mechanisms for the antigen specificity are incompletely understood. Here we explore the option that tumor-associated antigens (TAAs) may be transferred to antigen-presenting cells (APCs), together with immunosuppressive molecules, through cancer-derived small extracellular vesicles (sEVs), such as exosomes. Stimulation of a suppressive phenotype in the very same APCs that take up TAAs may yield antigen-specific tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 53 publications
(58 reference statements)
0
28
0
Order By: Relevance
“…Cancer-derived exosomes prevent the differentiation and activation of immune effector cells, modulate antigen expression, induce T cell apoptosis, and transport immunosuppressive cytokines. Recently, we provided evidence that melanoma-derived EVs were able to confer antigen-specific immunosuppression by simultaneously transporting MHC molecules presenting cancer-specific antigenic peptides and immunosuppressive cytokines [48]. Antigen-specific immunosuppression seems to occur during pregnancy as well and could be partially mediated by EVs.…”
Section: The Influence Of Pregnancy-associated Evs On the Maternal Immentioning
confidence: 99%
“…Cancer-derived exosomes prevent the differentiation and activation of immune effector cells, modulate antigen expression, induce T cell apoptosis, and transport immunosuppressive cytokines. Recently, we provided evidence that melanoma-derived EVs were able to confer antigen-specific immunosuppression by simultaneously transporting MHC molecules presenting cancer-specific antigenic peptides and immunosuppressive cytokines [48]. Antigen-specific immunosuppression seems to occur during pregnancy as well and could be partially mediated by EVs.…”
Section: The Influence Of Pregnancy-associated Evs On the Maternal Immentioning
confidence: 99%
“…The in-depth knowledge of the pleiotropic role of MTEX in the natural history of melanoma has a great potential clinical application in the disease diagnosis, treatment design, and prognosis of patient’s outcomes. MTEX are involved in a plethora of functions involved in initiation, progression, and metastasis of tumors, which is schematically depicted in Figure 2 (according to [ 26 , 37 , 73 , 74 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ,…”
Section: Biological Activity Of Mtexmentioning
confidence: 99%
“…However, in most of the studies reported in this context, melanoma cell lines were used as a source of MTEX. Düchler et al showed that cancer-induced immunosuppression was mediated by MTEX, and involved an antigen-specific mechanism [ 118 ]. The authors provided evidence that MTEX transferred MHC class I receptor proteins from cancer cells to the surface of antigen-presenting cells (APC).…”
Section: Biological Activity Of Mtexmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Düchler and colleagues used EVs derived from A375 human metastatic melanoma cells and observed different effects depending on the dendritic cell model used but down‐regulation of HLA class I and II was commonly observed 50 . They also showed that these melanoma‐derived EVs transfer HLA class I and TGF‐β to DCs, and the latter would be key to the immunosuppressive modulation observed 50 (Fig.…”
Section: Messages From Melanoma Cells To Immune Cellsmentioning
confidence: 99%